Proceedings of the 7th International Conference on Properties and Applications of Dielectric Materials (Cat. No.03CH37417)
DOI: 10.1109/icpadm.2003.1218391
|View full text |Cite
|
Sign up to set email alerts
|

Sensors for on-line PD detection in MV power cables and their locations in substations

Abstract: For developing a system capable of on-line detecting and localizing PDs in MV power cables, the choice of the sensor type is crucial. Sensors for detecting PDs can be divided into two main groups: capacitive and inductive sensors. In this paper, the advantages and disadvantages of these two types of sensors are discussed for on-line application. In multi-conductor cables, e.g. a three-phase belted cable, it is essential to distinguish the different propagation channels. When the cable is under normal operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…It has many advantages as compared to traditional condition monitoring systems. The major advantages are continuous monitoring, no disruption of power supply and system is working under normal conditions [26]. However, installing on-line on-site PD monitoring system is bit challenging because system is working at normal conditions and the noise produced by other instruments cannot be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…It has many advantages as compared to traditional condition monitoring systems. The major advantages are continuous monitoring, no disruption of power supply and system is working under normal conditions [26]. However, installing on-line on-site PD monitoring system is bit challenging because system is working at normal conditions and the noise produced by other instruments cannot be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…The sensor must be installed in an existing network, preferably during operation and may not introduce a safety risk during installation or operation. Therefore the choice was made to use inductive toroidal sensors, which can be clamped around the earth lead or the shielded cable itself, [8]. This has some important advantages: 1.…”
Section: A Sensor / Injector Unit (Pd-ol -Siu)mentioning
confidence: 99%
“…A survey of MV systems used in The Netherlands showed that for the majority of the substations, coupling sites are accessible for injecting or detecting signals by placing a coil either around a phase conductor at a cable end (where the earth screen is still present), or around the earth connection nearby the cable [4]. This inductive coupling scheme is basically a weakly coupled transformer.…”
Section: Transmission Line Descriptionmentioning
confidence: 99%
“…Sixteen cables in life circuits from two Dutch utilities have been tested at both sides to determine the noise level [4]. Commercially available inductive sensors with a bandwidth of several tens of megahertz were positioned at various locations interesting for PD detection, and accessible also for power line communication.…”
Section: Noise Levelmentioning
confidence: 99%
See 1 more Smart Citation